Between scientific capital and emotional capital: a cross-sectional study on the empathetic clinical gaze in Swedish medical education - Lena Halawi; Atika Khalaf (Frontiers in Medicine, 2026)
Introduction Clinical empathy was examined among Swedish medical students to understand how empathic engagement evolves during training. The study explored both quantitative patterns and qualitative reflections related to the Empathetic Clinical Gaze (ECG). Methods Clinical empathy was examined using a cross-sectional quantitative survey of 251 Swedish medical students with the Empathetic Clinical Gaze scale (ECG scale). To contextualize the quantitative findings, a secondary qualitative content analysis of brief to moderately reflective written comments from open-ended item evaluation prompts was carried out. Results Quantitatively, no significant gender or age differences in ECG were observed ( p > 0.05), while early-year students demonstrated higher ECG levels than those in later-years (39.1% vs. 25.5%; p = 0.030). Qualitatively, students described a growing tension between emotional resonance and clinical pragmatism. Early-year students emphasized affective engagement, whereas later-year students reported a shift toward cognitive empathy to manage diagnostic efficiency, workload pressures, and risks of emotional exhaustion. Two themes emerged: (1) Clinical detachment- The practice of applying empathy in a clinical context and (2) The application and significance of empathy in patient encounters. These themes reflect institutional and environmental influences that mirror global challenges in sustaining an empathetic clinical gaze during clinical training. Across groups, students described empathy as a context-dependent skill shaped by workload, time constraints, and professional norms. Discussion The study highlights the need for curricular strategies that support a sustainable empathetic clinical gaze, including longitudinal training, reflective practice, and scenario-based role-play. These findings contribute to international efforts to reconceptualize empathy as a dynamic, context-sensitive competency and offer actionable insights for educators seeking to address challenges in sustaining clinical empathy.